Design and construction of gym angkasa management website system in margoyoso village to improve customer service - Muzaki, Muhammad; Khotimah, Tutik; Meimaharani, Rizkysari (Journal of Soft Computing Exploration, 2025)
This study aims to design and implement a website-based gym management system at Angkasa Gym located in Margoyoso Village to improve customer service and operational efficiency. The current system is still manual, resulting in inefficiency and risk of errors in managing member registration, scheduling training sessions, and financial transactions. The proposed system is developed using the Waterfall model with stages of needs analysis, system design, implementation, testing, and maintenance. The Laravel framework was chosen because it supports the development of modern and secure web applications. The final system has key features such as user registration and login, trainer management, transaction processing, and review submission. Based on black box testing, all system functionality runs as expected. The results of the study indicate that the web-based system is able to significantly improve gym operational efficiency and improve user service experience. This study can be the basis for further development, such as automatic notifications, implemented in other gyms, and adaptation to the mobile application version.